Delivery of Nebulized Prebiotic/Postbiotic Formulations: Spatial Deposition and Exposure Characterization by GC–MS - Edoardo Cavalieri D’Oro; Claudio De Maio; Rita White; Enrico Greco (International Journal of Environmental Medicine, 2026)
Indoor environments are increasingly recognized as key determinants of human microbial exposure and skin health. Microbiome-aware interventions, including probiotic and prebiotic formulations, have been proposed to complement conventional environmental hygiene. However, quantitative data on the spatial distribution of nebulized prebiotic/postbiotic mixtures in enclosed spaces are lacking. The aim of this exploratory study was to characterize the aerosolization efficiency and spatial deposition of a prebiotic/postbiotic solution nebulized by two different devices in standardized indoor microenvironments. Two nebulizing devices were tested separately in two identical 20′ ISO containers (33.2 m3). A liquid prebiotic/postbiotic mixture at two concentrations (10% and 20% v/v in water) was nebulized for 1 or 2 h. Surface deposition was assessed using passive paper samplers placed at horizontal distances of 0, 25, 50, 100 and 200 cm from the aerosol outlet. A volatile chemical marker contained in the solution was quantified by gas chromatography–mass spectrometry to estimate deposited volume per unit area. Both devices generated detectable marker deposition at all distances, ranging from 0.22 to 14.42 µL·cm−2 of concentrate equivalent. In a mixed-effects model treating the individual run as the unit of replication, distance was the only factor reaching statistical significance, deposition decreasing approximately twofold per 100 cm (p < 0.001); the apparent effects of device type, concentration and run time did not reach significance. Spatial decay profiles were condition-dependent rather than systematically device-specific. Nebulized prebiotic/postbiotic mixtures can be delivered across meter-scale distances in enclosed indoor settings. Because each condition was tested in a single run, aerosol properties were not characterized and no microbiological or clinical endpoints were assessed; these findings represent a feasibility and exposure-characterization step rather than evidence of biological or health benefit, and they support further investigation of nebulized microbiome-modulating interventions in environmental and occupational medicine.